2019
DOI: 10.1002/jso.25738
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing cancer care for hepatocellular carcinoma at a safety‐net hospital: The value of a multidisciplinary disease management team

Abstract: Background Hepatitis C (HCV) is the primary etiology of hepatocellular carcinoma (HCC) in the US multidisciplinary disease management teams (DMT) that optimize oncologic care. The impact of DMT for HCC in safety‐net hospitals is unknown. Methods Patients diagnosed with HCC from 2009 to 2016 at Grady Memorial Hospital (GMH) were included. The primary aim was to evaluate referrals to care, receipt of therapy, and overall survival (OS) after DMT formation. Screening patterns of HCV patients for HCC were also exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…These data represent a marked improvement when contrasted with the baseline data that prompted the development of this screening program. The original analysis reported that only 23% of patients diagnosed with HCC from 2012 to 2016 had received any imaging exam within the year before diagnosis, 44% of patients presented with stage IV disease, and over 60% of patients diagnosed with HCC in this time period did not receive treatment 11. It is important to note when making this comparison that these were patients from throughout Grady Health System and not necessarily Liver Clinic patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These data represent a marked improvement when contrasted with the baseline data that prompted the development of this screening program. The original analysis reported that only 23% of patients diagnosed with HCC from 2012 to 2016 had received any imaging exam within the year before diagnosis, 44% of patients presented with stage IV disease, and over 60% of patients diagnosed with HCC in this time period did not receive treatment 11. It is important to note when making this comparison that these were patients from throughout Grady Health System and not necessarily Liver Clinic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The original analysis reported that only 23% of patients diagnosed with HCC from 2012 to 2016 had received any imaging exam within the year before diagnosis, 44% of patients presented with stage IV disease, and over 60% of patients diagnosed with HCC in this time period did not receive treatment. 11 It is important to note when making this comparison that these were patients from throughout Grady Health System and not necessarily Liver Clinic patients. Of 22 patients diagnosed with HCC during the first 3 years of this new initiative, only 16% presented with stage IV disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations